THE EFFECTIVENESS OF IMPLEMENTING THE LEARNING-BY-PLAY METHOD IN CHRISTIAN RELIGIOUS EDUCATION FOR PELITA KASIH PRESCHOOL CHILDREN IN PROBOLINGGO - Alex Frans Nathanael Nasution; Habakuk Sethio Ruku (Bethel Press, 2020)
This research is motivated by the principles of effective learning for early childhood. Where the learning developed is adapted to the psychology of early childhood. The theoretical basis of this research is the concept of playing while learning. The research technique used was qualitative research, where the sources were asked directly from teachers at PAUD Pelita Kasih in the city of Probolinggo. This form of interaction in the classroom is an approach to the teacher's creativity as an artist. As an artist, the teacher tries to create a pleasant classroom atmosphere through innovative learning methods. Therefore, this paper aims to discover that the learning method while playing can build student interaction. The research method used is descriptive qualitative. The research results show that the learning while playing method is innovative, creative, and helpful for increasing student interaction and supporting learning goals. In its application, teachers must also pay attention to the type of educational games used to implement the learning-by-play method.